2009
DOI: 10.1590/s0073-47212009000100010
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização citológica dos hemócitos de Anticarsia gemmatalis (Lepidoptera, Noctuidae) em larvas resistentes ao vírus AgMNPV

Abstract: ABSTRACT. Citological characterization of the Anticarsia gemmatalis (Lepidoptera, Noctuidae) hemocytes in resistant larvae to the virus AgMNPV. The occurrence of Anticarsia gemmatalis (Hübner, 1932) larvae resistant to the virus AgMNPV in laboratory led to the study of the hemocytes of this insect, in order to evalue its participation in the mechanisms which enables the resistance to the virus. The resistant larvae with 6 to 11 developmental days old (3 rd to 5 th instars) were anesthetized by cold and after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Negreiro et al [48] suggest that the defense of A. gemmatalis larvae to Baculovirus anticarsia (AgMNPV) may be attributed to higher hemocyte densities in the hemolymph. In support of this, we found that larvae reared in the presence of conspecifics were more resistant to this virus.…”
Section: Discussionmentioning
confidence: 99%
“…Negreiro et al [48] suggest that the defense of A. gemmatalis larvae to Baculovirus anticarsia (AgMNPV) may be attributed to higher hemocyte densities in the hemolymph. In support of this, we found that larvae reared in the presence of conspecifics were more resistant to this virus.…”
Section: Discussionmentioning
confidence: 99%
“…On the eighth and tenth day after starting bioassays with glyphosate and M. rileyi, and third and fifth day with novaluron, 3 μl of each insect hemolymph were collected by abdominal puncture diluted (2:1) in an anticoagulant solution. For the total and the differential hemocyte count (THC and DHC, respectively), the methodology was described by Negreiro et al (2009), in which fresh hemolymph was diluted 10 times with an anticoagulant solution (0.098 M NaOH, 0.186 M NaCl, 0.017 M EDTA, 0.041 M citric acid) and homogenized. The hemocytes were counted in a Neubauer chamber with optical microscope.…”
Section: Evaluation Of the Immune System Responsementioning
confidence: 99%